Method for manufacturing multi-layer structures
Patent Information
- Application Number
- JP2023562686
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-04-16
- Filing Date
- 2022-04-12
- Publication Date
- 2025-03-25
AI Technical Summary
Conventional polymers cannot withstand high temperatures required for manufacturing and operating advanced multilayer structures, leading to defects, cracking, and delamination due to differing thermal expansion coefficients of materials.
A method involving the use of preceramic polymers filled with inorganic particles to create a thick film layer with a controlled thermal expansion coefficient, allowing bonding with substrates to form a stable multilayer structure that can withstand high temperatures and thermal changes.
The method produces a multilayer structure with improved mechanical strength and thermal stability, enabling high-temperature applications without defects or delamination, and reduces production costs by avoiding pre-sintering or sintering processes.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to the manufacture of advanced substrates for applications in electronics (e.g. for MEMS), microelectronics, optoelectronics (e.g. for LEDs), RF power electronics, packaging and transfer handles. The present invention particularly relates to a method for the manufacture of multi-layer structures capable of withstanding high temperatures, in particular Semiconductor On Insulator (SeOI) structures providing a semiconductor layer separated from a supporting substrate by a thick film layer with modularity, for example for the integration of RF components. According to another aspect, the present invention also relates to a multi-layer structure obtainable by said manufacturing method. [Background technology]
[0002] The current trend towards ever-increasingly dense integration of components and miniaturization of devices increases the need for substrates with improved performance, especially with better heat dissipation and better resistance to temperature changes. The manufacture of increasingly complex structures can require annealing at temperatures reaching 1000 °C, not to mention operating temperatures that can reach 800 °C, especially in RF applications. The different materials required to create these multi-layer structures cause different expansions within the structure. This creates stresses that can lead to defects appearing, layers cracking, or layers peeling off. Due to these stresses, traditional polymers that can only withstand temperatures up to 400 °C cannot be used to bond between layers. Summary of the Invention
[0003] One of the objects of the present invention is to provide a method for the manufacture of a multilayer structure which overcomes at least one of the above mentioned obstacles. To this end, the present invention provides a method for the manufacture of a multilayer structure for applications in the field of microelectronics.
[0004] This manufacturing method is a) providing a first substrate; b) depositing a thick film layer of a precursor composition comprising a preceramic polymer filled with inorganic particles onto a first substrate; c) providing a second substrate; d) bonding the thick film layer to a second substrate; e) thinning the first substrate or the second substrate, in particular to obtain an active layer for obtaining an electronic device; f) subjecting the thick film layer to a pyrolytic heat treatment to ceramify the preceramic polymer to obtain a ceramic matrix composite material; Equipped with The loading rate and properties of the inorganic particles are selected such that, between room temperature and the pyrolysis temperature, the thick film layer has a thermal expansion coefficient that differs by up to 15% from the thermal expansion coefficient of the first substrate and the thermal expansion coefficient of the second substrate, preferably a thermal expansion coefficient that differs by up to 10% from the thermal expansion coefficient of the first substrate and the thermal expansion coefficient of the second substrate, for example a thermal expansion coefficient that differs by up to 5% from the thermal expansion coefficient of the first substrate and the thermal expansion coefficient of the second substrate.
[0005] In this way, the manufacturing method according to the invention allows to obtain a multi-layer structure in which the properties of the thick film layers, in particular the coefficient of thermal expansion (also known as CTE) can be adjusted to match the CTE of the first and second substrates, which can advantageously be used in processes or applications involving significant thermal changes.
[0006] A wide choice of preceramic polymers and inorganic particles allows the selection of the appropriate polymer for the desired multilayer structure, depending on its properties and its compatibility with the substrate on which it is deposited. In this case, the preceramic polymer and the inorganic particles are selected so that the composite material obtained after crosslinking and pyrolysis has a thermal expansion coefficient close to that of the first and / or second support. In this way, the constituent materials of the multilayer structure expand and contract in the same way during temperature changes, thereby avoiding loads in the structure that could damage the layer by the occurrence of defects, cracks or delamination of the layer. Depending on the inorganic particles used, the thick film layer may also be electrically insulating while having a high heat dissipation capacity. This is particularly suitable for regulating the temperature of the structure, particularly when the structure is used in applications involving transistor-type components whose operating temperatures can reach 800° C. In this way, the thick film layer according to the invention allows a high modularity.
[0007] Moreover, preceramic polymers have the advantage of good temperature resistance: in fact, preceramic polymers are organic / inorganic polymers that are commonly used to produce so-called PDC (short for Polymer Derived Ceramics) ceramic objects after heat treatment at high temperatures.
[0008] This allows the structure to be heat treated at high temperatures, for example in the case of repairing defects caused by the implantation of ionic species to thin the substrate, etc. In this way, the method ensures that the assembly of the multi-layer structure is stable throughout the manufacturing process of the multi-layer structure, in particular despite the step of pyrolysis of the preceramic polymer, and that it withstands the high operating temperatures (associated with the electronic components of the active layer).
[0009] The composite material thus obtained has sufficient mechanical strength for the desired application. The preceramic polymer is in fact a binder for the inorganic particles. After ceramification by pyrolysis, especially at around 1000 ° C, a ceramic matrix is formed in which the inorganic particles are embedded. The resulting PDC ceramic matrix is almost amorphous, in some cases completely amorphous, forming a binder for the inorganic particles which are uniformly distributed in the matrix without coalescing with each other. The pyrolysis also allows the thick layers to be compacted. Furthermore, for the intended application, pre-sintering or sintering of the ceramic, which is carried out at temperatures higher than the pyrolysis temperature, is not necessary, which advantageously reduces the production costs. Thus, the present manufacturing method allows the realization in a simple and reliable way of multilayer structures which are stable even at high temperatures and whose properties can be easily adjusted for the intended application.
[0010] "Active layer" means the layer of semiconductor material where electrical events take place.
[0011] "Ceramify" or "ceramization" and other derivative terms, as used herein, refers to the conversion of a preceramic polymer to an unsintered ceramic by pyrolysis.
[0012] Advantageously, the precursor composition of the thick layer deposited in step a) comprises inorganic particles with a filling rate of 50-80% by volume relative to the volume of the preceramic polymer. This filling rate allows the thick layer to have the desired properties, in particular the thermal expansion coefficient. It also allows the preceramic polymer to reduce dimensional losses during ceramification. In fact, the use of preceramic polymers leads to considerable dimensional changes during pyrolysis that allow the transformation of the polymer into ceramic. This leads to high mechanical residual stresses during the shaping of the preceramic polymer, which can cause defects, cracks and sometimes collapses in the layer. The presence of fillers therefore allows the volume loss to be reduced.
[0013] Furthermore, the loading remains low enough to allow for a sufficient amount of preceramic polymer to be present in the layer, which material maintains its role as a binder for the inorganic particles both before and after ceramization.
[0014] According to one configuration, the inorganic particles are chosen from among Si3N4, SiC, AlN, Al2O3 and mixtures of these inorganic particles, which, considered as such or as mixtures, are used to give the preceramic polymer and ceramic matrix a CTE close to that of the semiconductor material that can be used in the multilayer structure.
[0015] The size of the particles used varies from a few nm to 100 μm and is selected mainly depending on the desired layer thickness: for adhesion primer layers, sizes below 1 μm are preferred, whereas for thick layers of several hundred μm, the entire range can be used.
[0016] Specifically, the method includes a step of smoothing the surface and mechanically adjusting the thickness of the thick layer before the bonding step d) to a desired layer thickness. Typically, the thickness of the thick layer is 10 to 500 μm.
[0017] According to one possibility, the thick layer loses 20-50% of its original thickness during ceramification. The thickness of the thick layer before ceramification in step f) is 10-500 μm and after ceramification is 5-400 μm.
[0018] According to one aspect, the preceramic polymer of the precursor composition is selected from polysiloxanes, polycarbosilanes, polysilazanes, polyborosilanes, polysilsesquioxanes, polysilylcarbodiimides, polysilsesquicarbodiimides, polysilsesquiazanes, polyborosiloxanes, polyborosilazanes, and combinations of these polymers. The choice of the nature of the preceramic polymer depends on the desired properties for the desired multilayer structure, but also on the compatibility with the substrate on which the preceramic polymer is to be deposited.
[0019] Preceramic polymers derived from polysiloxanes, polycarbosilanes, polysilazanes may contain metals such as Hf, Zr, Ti, Al.
[0020] The desired ceramic matrix is SiO x C y (x is less than 2 and y is not zero), SiCN, Si(M)OC, Si(M)C, Si(M)CN, or SiBCN.
[0021] According to one possibility, step b) of depositing a thick layer is carried out by coating or screen printing when the precursor composition is liquid. To obtain a liquid precursor composition with the desired viscosity, a solvent can be added to the precursor composition. This is chosen from among xylene, MEK (Methyl Ethyl Ketone or 2-butanone solvent, available for example from Sigma Aldrich, Spelco...), Diestone DLS (solvent composition offered by the company Socomore).
[0022] According to another possibility, when the precursor composition is solid, step b) of depositing the thick layer is carried out by hot pressing.
[0023] Preferably, when the first and second substrates are made of silicon, the preceramic polymer used is SILRES® MK POWDER, the inorganic particles are SiC, and the whole results in a ceramic with a CTE very close to that of silicon.
[0024] According to a specific embodiment of the method of the present invention, the first substrate and the second substrate are made of silicon, and the precursor composition is prepared by mixing 2-4 wt. % of SILRES MK POWDER preceramic polymer with 65-72 wt. % of SiC inorganic particles and 24-33 wt. % of a solvent such as Diestone DLS solvent.
[0025] Instead of SiC, a mixture of inorganic particles may be used, for example 75-85% Si3N4 mixed with 15-25% Al2O3.
[0026] Mixtures of 45-70% Si3N4 with 30-55% AlN also make it possible to obtain thick layers with a CTE difference of less than 10% with silicon.
[0027] Advantageously, the bonding between the thick film layer and the second substrate in step d) is performed via an adhesion primer layer preformed on the second substrate and / or on the thick film layer. This layer allows improving the bonding energy between the material of the thick film layer and the material of the second substrate. This contributes to the mechanical strength of the multilayer structure when it undergoes mechanical steps such as mechanical thickness rectification. The selection of the properties of the primer layer is made in order to provide resistance to pyrolysis temperatures and to obtain good adhesion with the thick film layer. Thus, the primer layer is selected from among preceramic polymers present in liquid or solid form, with the possibility of adding solvents to adjust the viscosity and facilitate application.
[0028] According to one possibility, the adhesion primer layer has a thickness of 1-10 μm. This thickness is sufficient to act as a bonding agent, beyond which cracks are likely to occur. The precursor composition preformed on the second substrate and / or on the thick film layer comprises an adhesion preceramic polymer material, such as SILRES H62C polysiloxane available from Wacker.
[0029] Preferably, when the adhesive preceramic polymer is deposited on the second substrate, the second substrate is precrosslinked before contacting it with the thick film layer in order to allow good bonding. This step is carried out at a temperature below the crosslinking temperature of the polymer considered. This step consists of stabilizing the preceramic polymer, which allows it to reach a state immediately preceding the thermosetting state of the polymer. At this stage, the polymer is deformable but cannot be solubilized. In fact, the precrosslinked adhesive preceramic polymer has some non-crosslinked functions which allow it to bond to the thick film layer.
[0030] When the adhesion primer layer is deposited on the thick film layer, the preceramic polymer of the thick film layer is pre-crosslinked beforehand, for example by heat treatment at a temperature lower than the crosslinking temperature of the preceramic polymer, typically 50-400°C.
[0031] According to a variant in which the adhesive preceramic polymer (of the adhesive primer layer) is in the form of a solid powder, for example SILRES MK POWDER, it can be distributed onto the thick film layer. When the powder melts, bonding takes place.
[0032] Alternatively, the adhesive primer layer contains a loading of up to 50% of the total volume of the adhesive preceramic primer, which not only limits the volume shrinkage during crosslinking of the adhesive polymer, but also allows the primer layer to be functionalized depending on the nature and loading of the loading, for example, electrical conductivity with Cu, Ag, Al or thermal conductivity with SiC, AlN, BN.
[0033] Preferably, the bonding in step d) comprises a step of contacting the thick film layer with the second substrate to form a stack and a step i) of hot pressing said stack. This step allows to increase the bonding energy between the thick film layer and the second substrate, to increase the mechanical strength of the stack leading to a multi-layer structure and to stabilize the bond. It is understood herein that the contact can be made by direct contact of the thick film layer with the second substrate or by indirect contact obtained through an adhesion primer layer as described above.
[0034] According to one possibility, the hot pressing step i) comprises a crosslinking heat treatment at temperatures varying between 100 and 400 °C and a pressure of less than 500 kPa in order to obtain crosslinking of the preceramic polymer of the thick-film layer. The use of pressure makes a laborious surface preparation step before bonding unnecessary, but nevertheless, the higher the pressure, the more the surface must be flat and free of dust in order to avoid damage to the substrate. Furthermore, if appropriate, the adhesive preceramic polymer is also crosslinked by this step.
[0035] In the particular case of using SILRES MK POWDER preceramic polymers, the crosslinking heat treatment is carried out with a heating gradient of 0.1-20° C. / min, preferably 0.5-5° C. / min, for example 1° C. / min.
[0036] According to one possibility, the thinning of step e) of the method is obtained by the Smart Cut® technology, the method comprising, before step b), a step a1) of implanting ionic species in the first substrate to create a weakened surface, the thinning step e) comprising a step of breaking along the weakened surface.
[0037] The fracture step can be obtained by a thermal treatment followed by a mechanical load or without mechanical load. The fracture process is then usually followed by a pyrolysis heat treatment in a neutral atmosphere, such as under argon, to strengthen the bonded interface. A heating gradient is appropriately applied depending on the layer thicknesses, the thermal expansion coefficients and the materials considered, to avoid deformation of the structure.
[0038] The hot pressing step i) can, if appropriate, contribute to the adiabatic breakdown of step e).
[0039] According to one possibility, the method comprises, after the implantation step a1), a step a2) of depositing a hardening layer on the implanted surface. Preferably, the hardening layer is deposited before the step b) of depositing the thick film layer.
[0040] Preferably, the stiffening layer is formed of Si3N4 by a low temperature deposition technique such as PECVD at 300°C to a thickness of 500 nm to 4 μm. The stiffening layer material is stable at pyrolysis temperatures and has a CTE close to that of the substrate. Furthermore, the deposition conditions used maintain the implanted region so as not to cause fracture at this stage of the method.
[0041] Alternatively, the method includes, before step b) of depositing the thick-film layer, depositing a complementary adhesion primer layer made of a preceramic polymer on the hardening layer in order to improve the contact between the thick-film layer and the hardening layer. This complementary adhesion primer layer also provides a complementary hardening effect. The thickness of the hardening layer can be reduced accordingly.
[0042] According to the alternative of step e), which is carried out by breaking, the method comprises a thinning by mechanical thickness adjustment in order to obtain an active layer thickness of 10 to 140 μm, preferably 20 to 120 μm, for example 90 to 110 μm.
[0043] Advantageously, step f) of the method comprises a vacuum pyrolysis heat treatment in the presence of nitrogen or argon. The pyrolysis is carried out in a controlled atmosphere. For example, pyrolysis in the presence of oxygen in air produces undesirable oxides, often in the form of powders. The temperature of the pyrolysis heat treatment is below the sintering temperature of the ceramic matrix. It depends on the nature of the preceramic polymer used.
[0044] According to a second aspect, the invention provides a multilayer structure for applications in microelectronics, comprising a thick-film layer arranged between an active layer and a support substrate consisting of one of a first substrate and a second substrate, the active layer resulting from thinning the other of the first substrate and the second substrate, the thick-film layer comprising or consisting of a composite material comprising or consisting of a ceramic matrix derived from a polymer and inorganic particles, the nature and filling rate of the inorganic particles of the composite material being selected such that the thick-film layer has a CTE that differs from the CTE of the material of the support substrate and the CTE of the active layer by at most 15%, in particular from the CTE of the material of the support substrate and the CTE of the active layer by at most 10%, for example from the CTE of the material of the support substrate and the CTE of the active layer by at most 5%.
[0045] The multilayer structure thus constructed has excellent mechanical strength between room temperature and the operating temperature, for example, between 800 and 1000°C.
[0046] In this specification, ceramics of the ceramic matrix are understood to be ceramics derived from polymers resulting from the pyrolysis of preceramic polymers filled with inorganic particles. Said ceramic matrix is completely free of sintering. It is usually amorphous, sometimes completely amorphous, unlike sintered ceramics, which are usually polycrystalline.
[0047] Preferably, the first and second substrates are made of the same material.
[0048] According to one configuration, the first substrate and / or the second substrate are made of single crystal silicon.
[0049] According to one possibility, the material of the active layer is selected among monocrystalline materials in order to optimize the performance of the component.
[0050] According to another possibility, the multilayer structure comprises an active layer and a support substrate made of silicon, the thick layer being made of SiO x C y(x is less than 2 and y is not zero) and the inorganic particles are SiC.
[0051] According to other features, the method for producing the multi-layer structure of the present invention, and the multi-layer structure itself, comprise one or more of the following optional features, taken alone or in combination: The thick layer has a thickness of 10 to 500 μm. Above that, there is an increased risk of cracks occurring during ceramization (i.e. pyrolysis). The ceramified thick-film layer, i.e. the thick-film layer comprising ceramic matrix composite and inorganic particles, has a thickness of about 5-400 μm. The thick film layer is bonded to the supporting substrate or to the active layer via an adhesion primer layer. The adhesion primer layer is formed from polysiloxane preceramic polymers such as SILRES H62C and SILRES MK POWDER. The adhesion primer layer is formed from a composition comprising a polysiloxane preceramic polymer of SILRES H62C in a proportion of 70-80% by weight, diluted with Diestone DLS solvent in a proportion of 20-30% by weight. The adhesive primer layer has a thickness of 1 to 10 μm. The active layer has a thickness of 1.4 to 100 μm. The active layer obtained by thinning through fracture preferably has a thickness of 1.4 to 1.6 μm. When produced by thinning of the first or second substrate by mechanical thickness adjustment, the active layer has a thickness of 10 to 100 μm. the material of the first and second substrate is selected from semiconductor materials, in particular Si, Ge, GaN and / or SiC; The materials of the first and second substrate consist of two materials with different properties. The materials of the first substrate and the second substrate consist of two materials of the same nature. The material of the first substrate and / or the second substrate is monocrystalline.
[0052] The multilayer structure thus formed can be subjected to processes for the manufacture of electronic components, such as mechanical thickness adjustment, thinning, chemical mechanical polishing, etching, deposition of a dielectric or metal, deposition of at least one layer including an active layer to obtain at least one electronic component, patterning, passivation, heat treatment, or at least one combination of these processes.
[0053] Other aspects, objects and advantages of the invention will become more apparent on reading the following description of two embodiments, given by way of non-limiting example, with reference to the attached drawings, in which the figures do not necessarily correspond to the size of all the elements shown, in order to make them more legible. In the figures, dotted lines are used to clearly and clearly indicate the weakened surfaces of the material layers in continuous form. In the following description, for the sake of simplicity, identical, similar or equivalent elements of the different embodiments are provided with the same reference numbers. [Brief description of the drawings]
[0054] [Figure 1] FIG. 2 shows a schematic diagram of step a1) of implanting a first substrate according to a first embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram illustrating step a2) of depositing a hardening layer according to a first embodiment of the present invention. [Diagram 3] FIG. 3 is a schematic diagram illustrating step b) of depositing a thick layer according to a first embodiment of the present invention. [Figure 4] FIG. 3 is a schematic diagram illustrating step c) of providing a second substrate covered with an adhesion primer layer according to a first embodiment of the present invention. [Diagram 5] FIG. 2 is a schematic diagram illustrating step i) of hot-pressing a thick film layer in contact with a second substrate according to a first embodiment of the present invention. [Figure 6] FIG. 2 is a schematic diagram illustrating step e) of thinning along the weakened surface according to a first embodiment of the present invention. [Figure 7] FIG. 1 is a schematic diagram showing a multilayer structure obtained according to a first embodiment of the present invention. [Figure 8]FIG. 5 is a schematic diagram illustrating step b) of depositing a thick layer according to a second embodiment of the present invention. [Figure 9] FIG. 9 is a schematic diagram illustrating hot-pressing step i) according to the embodiment of FIG. 8. [Figure 10] FIG. 9 is a schematic diagram illustrating the thinning step e) according to the embodiment of FIG. 8. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0055] A first embodiment of the method of the invention is illustrated in figures 1 to 7, in which a multi-layer structure 100 is obtained by the Smart Cut technology. To do so, as illustrated in figure 1, a first substrate 1 made of silicon is prepared (step a) and hydrogen ions are implanted with an energy of 160 keV (step a1) in order to obtain a weakened surface 2 at a considerable depth in the substrate 1. Then, a step a2) is performed, depositing a hardening layer made of Si3N4 on the implanted surface of the first substrate 1. The deposition is carried out using a low-temperature technique such as PECVD at 300 °C, to a thickness of about 4 μm. The CTE of the hardening layer 3 thus constituted is about 3.3 × 10 -6 / °C, which is similar to the CTE of silicon.
[0056] According to FIG. 3, the thick film layer 4 is a composite of 30 vol. % polysiloxane preceramic polymer and 70 vol. % SiC inorganic particles (CTE is 4-4.5×10 according to the matweb.com website). -6 / ° C. (total volume of dry precursor composition is 100%). According to another variant not shown, the volume filling rate of the inorganic particles is 50-70% by volume, depending on the nature of the particles and on the material of the substrate considered.
[0057] More specifically, the precursor composition is prepared by mixing about 2.4% by weight of SILRES MK POWDER polysiloxane preceramic polymer, provided in powder form by Wacker, with about 27.9% by weight of Diestone DLS solvent and 69.7% by weight of SiC inorganic particles. The CTE of this precursor composition is less than 10% different from that of silicon, and according to J. Haisman (Applied Optics 1999), the value is 3-4×10 at 200-1000° C. -6 / °C. According to another variant, the SiC inorganic particles are Si3N4 (CTE is 3.3×10 -6 / ℃) and 15-25% by volume of Al2O3 (CTE is 8.2×10 -6 / °C). According to yet another variant, the SiC inorganic particles are replaced by a mixture of 45-70% by volume of Si3N4 and 30-55% by volume of AlN (according to the MatWeb website, at 25-1000°C, the CTE is 5.5×10 -6 / °C) mixture.
[0058] The solvent of the thick layer 4 is then evaporated at room temperature and the thick layer 4 is mechanically trimmed to a desired thickness and to provide a flat surface. Typical thicknesses of the thick layer 4 are 10-500 μm after the solvent has evaporated, depending on the desired application.
[0059] According to a variant not shown, the solvent is evaporated in an oven set at 30-100°C.
[0060] According to another variant not shown, the deposition of the thick layer 4 is carried out by hot pressing, when the precursor composition based on SILRES MK POWDER and SiC is solvent-free.
[0061] According to step c) of the method, as shown in FIG. 4, a second silicon substrate 5 is prepared. To facilitate bonding with the thick film layer 4, an adhesion primer layer 6 is deposited on the surface, reaching a thickness of 10 μm. This primer layer is selected among adhesion preceramic polymers in order to withstand high heat treatments and to facilitate adhesion and bonding with the thick film layer 4, which is itself made of a preceramic polymer. Here, it is SILRESR H62C polysiloxane (75% by weight of the total precursor composition), available in liquid form from the supplier Wacker, diluted with Diesstone DLS solvent (25% by weight of the total precursor composition). According to other possibilities not shown, the precursor composition of the adhesion primer layer 6 is reinforced with metal, ceramic or polymer particles, depending on the desired properties and / or to reduce the volumetric shrinkage during pyrolysis.
[0062] This adhesion primer layer 6 is subjected to a pre-crosslinking step by heat treatment at a temperature of 175° C. for 1 hour. This step allows the adhesion preceramic polymer to be pre-cured below the crosslinking temperature and to give it adhesion properties that allow bonding to the thick-film layer 4 without diffusing into it. According to an alternative configuration not shown, the adhesion primer layer 6 is deposited on the previously pre-crosslinked thick-film layer 4 for bonding to the second support substrate 5.
[0063] According to yet another variant not shown, an adhesion primer layer 6 is deposited on the hardened layer 3 before the deposition of the thick-film layer 4, which not only allows good adhesion between the hardened layer 3 and the thick-film layer 4, but also fills the voids in the thick-film layer 4 and completes the hardening effect of the hardened layer 3.
[0064] According to another possibility not shown, the method does not include a step of forming an adhesion primer layer 6, and depending on the properties and conditions of the selected material, even in the absence of this layer it is possible to obtain sufficient bonding energy for the desired subsequent operation.
[0065] According to step d) of the method illustrated in FIG. 5, the thick film layer 4 is brought into contact with a second substrate 5 via an adhesion primer layer 6 to form a stack 10. The stack 10 is then subjected to step i) of hot pressing for 4 hours. The applied pressure is 470 kPa and the heat treatment is carried out at a temperature of 200° C. allowing crosslinking and initial compaction of the SILRES MK POWDER and SILRES H62C. The crosslinking temperature is conventionally applied by a heating gradient of 0.1 to 20° C. / min. In this embodiment it is 1° C. / min.
[0066] A thinning step e) is then performed by applying a thermal budget to separate along the weakened surface 2, as shown in figure 6. In this embodiment, a thermal budget is applied with a heating gradient of 5°C / min, with stages at 300°C and 500°C for 1 hour. In this way, an active layer 7 of silicon with a thickness of 1.5 μm is obtained.
[0067] Finally, as shown in FIG. 7, the method includes a step f) of pyrolysis heat treatment in an argon atmosphere with a heating gradient of 1° C. / min up to 1000° C. with two stages of 1 h of free ramping at 600° C. and 800° C., respectively, until the ceramification temperature of the SILRES MK POWDER is reached. The heat treatment at 1000° C. also allows the implantation defects in the silicon to be repaired. The thick layer 4 is also compressed, approximately half its original thickness. In this way, a multilayer structure 100 is obtained, which includes, from the surface to the base, an active layer 7 made of silicon, a hardened layer 3 of Si3N4, a thick layer 4 of amorphous ceramic matrix composite material, not sintered and filled with SiC particles, an adhesion primer layer 6 and a second silicon substrate 5.
[0068] A second embodiment of the invention will now be described with reference to figures 8 to 10. This embodiment differs from the previous one in particular in that the thinning step e) is obtained by a mechanical thickness adjustment operation of the first substrate 1 or the second substrate 5. As shown in figure 8, a thick layer 4 of a precursor composition is deposited by screen printing on a first monocrystalline silicon substrate 1. This precursor composition consists of a mixture of SILRES MK POWDER (50% by volume) and inorganic particles of Si3N4 and Al2O3 (50% by volume) in a proportion of 80 / 20 respectively, to which Diestone DLS solvent is added to reach the desired viscosity for deposition by screen printing. After drying of the solvent at room temperature, a second polycrystalline silicon substrate 5 covered with an adhesion primer layer 6 made of a pre-crosslinked preceramic polymer is prepared for contact and bonding with the thick layer 4. To stabilize the stack 10 obtained, a step i) of hot pressing is performed at the crosslinking temperature of the preceramic polymer (figure 9). Then, a step e) of mechanical thickness adjustment is performed on the first substrate 1 in order to obtain an active layer 7 made of monocrystalline silicon with a thickness of about 20 μm. It should be noted that in the case of thinning by mechanical thickness adjustment, the hardening layer 3 is not necessary. A pyrolysis treatment at 1000° C. is performed (step f) with a heating gradient of 1° C. / min, including two stages at 600° C. and 800° C. Each of the two stages lasts for 1 h, during which the temperature is allowed to fall freely. In this way, a multilayer structure 100 is obtained, which includes, from the base to the surface:
[0069] a support substrate consisting of a second substrate 5 covered with an adhesion primer layer 6 a thick layer 4 of amorphous SiOC ceramic matrix composite, without sintering, containing inorganic fillers of Si3N4 and Al2O3 and having a thickness of 100 μm, and - an active layer 7 made of single crystal Si and having a thickness of 20 μm Preferably, the thick film layer 4 has a CTE that differs from the CTE of the material of the supporting substrate by at most 15% (FIG. 10).
[0070] Thus, the present invention provides a method for the manufacture of multi-layer structures that can be easily implemented. By selecting the nature and thickness of the layers, the structure has the ability to withstand high temperatures and to dissipate significant heat. By proper selection of the preceramic polymers used, as well as the selection of the rate and nature of the inorganic filler, it is possible to obtain other properties while preserving the desired properties regarding the CTE of the different layers.
Claims
1. A method for the manufacture of a multi-layer structure (100) for applications in the microelectronics field, comprising: a) providing a first substrate (1); b) depositing a thick film layer (4) of a precursor composition comprising a preceramic polymer filled with inorganic particles onto said first substrate (1); c) providing a second substrate (5); d) bonding the thick film layer (4) and the second substrate (5); e) thinning the first substrate (1) or the second substrate (2) to obtain an active layer (7); f) subjecting the preceramic polymer of the thick film layer (4) to a pyrolytic heat treatment in order to ceramify the preceramic polymer to obtain a ceramic matrix composite material; Equipped with The filling rate and properties of the inorganic particles are selected such that the thick film layer (4) has a thermal expansion coefficient that differs by at most 15% from the thermal expansion coefficient of the first substrate (1) and the thermal expansion coefficient of the second substrate (5) between room temperature and pyrolysis temperature.
2. 2. The method for producing a multilayer structure (100) according to claim 1, wherein the bonding between the thick film layer (4) and the second substrate (5) in step d) is performed via an adhesion primer layer (6) preformed on the second substrate (5) and / or on the thick film layer (4).
3. 3. A method for manufacturing a multilayer structure (100) according to claim 1 or 2, wherein the bonding of step d) comprises the steps of contacting the thick film layer (4) with the second substrate (5) to form a stack (10) and i) hot pressing the stack (10).
4. The method for producing a multilayer structure (100) according to claim 1 or 2, wherein the precursor composition comprises inorganic particles at a loading of 50-80% by volume relative to the volume of the preceramic polymer.
5. The inorganic particles are Si 3 N 4 , SiC, AlN, Al 2 O 3 and mixtures of these inorganic particles.
6. 3. The method of claim 1 or 2, wherein the preceramic polymer of the precursor composition is selected from the group consisting of polysiloxanes, polycarbosilanes, polycarbosiloxanes, polysilazanes, polysilsesquioxanes, polysilylcarbodiimides, polysilsesquicarbodiimides, polysilsesquiazanes, polyborosilanes, polyborosiloxanes, polyborosilazanes, and combinations of these polymers.
7. 3. A method for producing a multilayer structure (100) according to claim 1 or 2, wherein the step b) of depositing the thick film layer (4) is carried out by coating or screen printing, when the precursor composition is liquid.
8. 3. The method according to claim 1 or 2, further comprising, prior to step b), a step a1) of implanting ion species into the first substrate (1) to form a weakened surface (2), and wherein the thinning step e) comprises breaking along the weakened surface (2).
9. 9. The method according to claim 8, further comprising, after said implanting step a1), a step a2) of depositing a hardening layer (3) on the surface implanted with said ionic species.
10. The method according to claim 1 or 2, wherein the thinning step e) is performed by mechanical thickness adjustment in order to obtain a thickness of the active layer (7) between 10 and 140 μm.
11. A multilayer structure (100) for applications in microelectronics, comprising: The multilayer structure (100) comprises a thick film layer (4) provided between an active layer (7) and a support substrate consisting of one of a first substrate (1) and a second substrate (5), the active layer (7) is formed by thinning the other of the first substrate (1) and the second substrate (5); The thick film layer (4) comprises a composite material including a ceramic matrix and inorganic particles; The properties and loading of the inorganic particles are selected such that the thick film layer (4) has a CTE that differs by at most 15% from the CTE of the material of the supporting substrate and the CTE of the active layer (7).
12. An intermediate structure for the pyrolytic formation of a multilayer structure (100) according to claim 11, comprising The intermediate structure comprises a thick film layer (4) disposed between an active layer (7) and a support substrate consisting of one of a first substrate (1) and a second substrate (5); the active layer (7) is formed by thinning the other of the first substrate (1) and the second substrate (2); The thick film layer (4) comprises a preceramic polymer filled with inorganic particles; The characteristics and loading of inorganic particles are selected such that, between room temperature and the pyrolysis temperature of the preceramic polymer, the thick film layer (4) has a CTE that differs by a maximum of 15% from the CTE of the material of the supporting substrate and the CTE of the active layer (7).